An Experimental Model of Obsessive-Compulsive Disorder Based on Verbal and Nonverbal Responses (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
The current study demonstrates an experimental model of obsessive-compulsive disorder using a single subject design with 16 verbally skilled participants without clinical diagnosis. Experiments 1 and 2 show a model of obsessive-compulsive disorder based on some functional relations established between instructions, a task of separating seeds and the non-verbal checking responses.  We investigated whether instructions specifying aversive or appetitive consequences could increase the percentage of checking responses. In Experiment 1, five of the eight participants increased their checking responses when they received instructions that specified an aversive consequence.  In Experiment 2, seven of the eight participants showed an increase when they received instructions that specified an appetitive consequence.  We concluded that the instructions altered the discriminative and/or motivating function of the stimuli involved in the experimental task.
Keywords: rule-governed behavior, instructional control, verbal behavior, behavioral disorders, experimental design